POLITIK HUKUM DIUNDANGKANNYA QANUN NOMOR 11 TAHUN 2018 TENTANG LEMBAGA KEUANGAN SYARI’AH (LKS) DI PROVINSI ACEH - Rachmatika Lestari; Eza Aulia; Dara Quthni Effida (Prodi Ilmu Hukum, Universitas Teuku Umar, 2021)
In the section weighing Qanun Aceh Number 11 of 2018 on Islamic Financial Institutions (LKS) states that the juridical reason of the establishment of Qanun LKS is a follow-up to the implementation of Article 21 Qanun Aceh Number 8 of 2014 on the Principals of Islamic Shari'ah. After the promulging of Qanun LKS, many Conventional Bank Financial Institutions in Aceh decided to close their business in Aceh, so that if people still want to use conventional bank services, then the transaction must be done outside Aceh. In fact, almost all business actors in Aceh's economic activities are connected to outside areas, while in outside areas many business actors, especially corporations, have not fully used the Shari'ah banking system. The formulation of the problems discussed in this study is: